Evaluasi Standar Pelayanan Sosial Pengasuh Di Panti Asuhan Yayasan Anugrah Kasih Abadi - Narma Simbolon; Fajar Utama Ritonga (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
This study aims to describe the social service program for children at the Anugrah Kasih Abadi orphanage, evaluate the social service programs that have been carried out, and analyze the driving and inhibiting factors in the implementation of the children's social service program at the Anugrah Kasih Abadi Foundation orphanage. This research is descriptive. This study uses an evaluation method, the results of the study indicate that social services at the Anugrah Kasih Abadi Foundation orphanage are lacking. There are four types of services found, namely physical and health services, education services, mental spiritual services, and skills guidance services. Anugrah Kasih Abadi Orphanage is one of the privately owned orphanages that was established in 2008, the number of children in the Anugrah Kasih Abadi Orphanage is 61 people including 30 boys and 31 girls and 6 caregivers. The results of the study are that planning is carried out before the implementation of social service activities for children in orphanages. The involvement of all elements in planning is very important both, providing guidance and direction to foster children. Always supervised by both the caretaker of the orphanage and by the teacher who teaches.